The IMPLEMENTATION OF THE SCHOLARSHIP PROGRAMS AMONG THE STUDENT GRANTEES AND SCHOLARS OF KALINGA STATE UNIVERSITY - Reyes, Paulino (IJRDO - Journal of Social Science and Humanities Research, 2019)
The descriptive research looked into the implementation of the scholarship programs of the Kalinga State University.It specifically sought answers on the extent of implementation of the scholarship programs among the student grantees of Kalinga State University; the extent of the benefits derived from the scholarship programs encountered by the student grantees; and the degree of seriousness of the problems encountered by the student grantees in the implementation of the scholarship programs. Responses to the questionnaire were treated using a three-point scale, quantified through the weighted mean and further analyzed using Analysis of Variance (ANOVA). The t-Test was used to determine the significant differences along the variable of gender. The 120 student grantees of the Kalinga State University were the respondents of the study. It was found that the implementation of the scholarship programs by the scholars were perceived as much implemented, the scholars were moderately benefited by the scholarship programs and the problems encountered by the student grantees were moderately serious. It is recommended that the Sibling scholarship and DA-ACEF should be well- emphasized during orientation, the students should maintain the cut-off grade to enjoy their scholarship, the granting of scholarship should be based on the scholastic performance of the students, processing of scholarship papers should be improved by sponsoring agency, slots for scholarship programs should be properly disseminated, strict implementation in the implementation of scholarship grants, and the selection and approval of application should be based on the sound principle of ‘first come, first serve’ basis and the qualification of the applicants.